Length-weight relationship and condition factor of karut croaker Johnius carutta, Bloch, 1793 off Visakhapatnam coast - Swamy Kumar, M.; Rajeswari, G.; Sreeramulu, K.; Kishore, B. (Indian Journal of Fisheries, 2014)
Length-weight relationship (LWR) and condition factor (K) of karut croaker Johnius carutta , Bloch, 1793 was studied using 3,406 specimens (1718 males and 1688 females) ranging in length from 11.00 to 24.50 cm collected from Visakhapatnam coast. Regression equation was calculated for males as: Log W=-1.4879 + 2.6801 Log L (R 2 = 0.81), for females as Log W=-1.3327 + 2.5651 Log L (R 2 = 0.78) and for pooled data as: Log W=-1.4378 + 2.6448 Log L (R 2 = 0.80) indicating negative allometric growth. The values of K were found to be above one in all the months in both sexes, and the value is influenced by gonadal maturity, spawning season and feeding rate of fish.